2011
DOI: 10.1002/pros.21392
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine tumor cells in prostate cancer: Evaluation of the neurosecretory products serotonin, bombesin, and gastrin – impact on angiogenesis and clinical follow‐up

Abstract: NETC have an influence on angiogenesis and are correlated with the clinical-pathological parameters. A high expression of NETC is associated with an early failure of treatment. Our study underlines the importance of NETC in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
0
17
0
3
Order By: Relevance
“…Moreover, we also nin in cholangiocarcinoma, which stimulate cholangiocarcinoma cell growth, and this condition is responsive to the blockade by the inhibition of serotonin synthesis (50,52). In contrast, serotonin by itself plays a marginal role in regulating the growth of PCa cells in general (53), and there was no significant clinical correlation of serotonin levels with PCa disease progression (54,55). The different effects of serotonin in diverse cancers therefore also provide insights into the differential functions of MAOA in PCa and other cancers.…”
Section: Figure 11mentioning
confidence: 91%
“…Moreover, we also nin in cholangiocarcinoma, which stimulate cholangiocarcinoma cell growth, and this condition is responsive to the blockade by the inhibition of serotonin synthesis (50,52). In contrast, serotonin by itself plays a marginal role in regulating the growth of PCa cells in general (53), and there was no significant clinical correlation of serotonin levels with PCa disease progression (54,55). The different effects of serotonin in diverse cancers therefore also provide insights into the differential functions of MAOA in PCa and other cancers.…”
Section: Figure 11mentioning
confidence: 91%
“…For patients with known CRPC and clinical suspicion of SCC, treatment can be selected on the basis of clinical features if tissue is not readily accessible or if it is unsafe to wait for a pathological diagnosis. Increased expression of plasma CgA—along with other plasma markers, such as CEA, Ca19.9, neuron-specific enolase, bombesin, 5-hydroxytryptamine, and gastrin—might provide supporting evidence for the diagnosis of prostatic SCC, 40,54,59,60 and could have a role in monitoring response to therapy. Many questions relating to the optimal use of serum neuroendocrine and epithelial markers remain unanswered and there is no consensus regarding their use in routine clinical practice.…”
Section: Diagnostic Work-upmentioning
confidence: 99%
“…Current work has shown that patients with Gleason score 8–10 prostate cancer that have >1% NE positive diseases have inferior clinical outcomes when they are treated with radiotherapy due to an increase in distant disease failure [26]. The number of NE positive cells was correlated with the Gleason score and high numbers of NE positive cells were associated with early treatment failure [27]. As noted above obesity has been associated with increased risk of more aggressive prostate cancer, higher rates of biochemical relapse, and prostate cancer-specific death.…”
Section: Introductionmentioning
confidence: 99%